Promoting systems thinking through perspective taking when using an online modeling tool - Jordan, Rebecca C.; Gray, Steven; Boyse-Peacor, Alita; Sorensen, Amanda E.; Frantz, Cynthia McPherson; Jauernig, Johanna; Brehm, Paul; Shammin, Md Rumi; Petersen, John (Frontiers in Education, 2023)
Introduction Disagreements between people on different sides of popular issues in STEM are often rooted in differences in “mental models,” which include both rational and emotional cognitive associations about the issue; especially given these issues are systemic in nature. Methods In the research described here, we employ the fuzzy cognitive mapping software MentalModeler (developed by one of the authors)1 as a tool for articulating implicit and explicit assumptions about one’s knowledge of both the environmental and social science and values underpinning complex system related issues. More specifically, we test the assumption that this pedagogical approach will foster certain aspects of perspective taking that can be traced with cognitive development and systems thinking as students not only articulate their own understanding of an issue, but also articulate the view of others. Results and discussion Results are discussed with respect to systems thinking that is developed through this type of modeling.